2018
DOI: 10.4274/jcrpe.0029
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Features of the Prader-Willi Syndrome; The Case for Making the Diagnosis During the First Week of Life

Abstract: Objective:Early diagnosis is of proven benefit in Prader-Willi syndrome (PWS). We therefore examined key perinatal features to aid early recognition.Methods:Data were collected from case records of subjects attending a multi-disciplinary clinic and from a retrospective birth questionnaire.Results:Ninety patients (54 male-36 female) were seen between 1991-2015, most with paternal deletion (n=56) or maternal isodisomy (n=26). Features included cryptorchidism in 94% males, preterm birth (26%), birthweight <2500 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
(56 reference statements)
8
14
0
Order By: Relevance
“…The prevalance of preterm birth, SGA and LBW in our cohort was 17.3%, 40.3% and 42.3%, respectively, which was in concordance with the increased incidence of preterm birth, LBW and intrauterine growth retardation reported in PWS ( 26 , 27 , 28 ).…”
Section: Discussionsupporting
confidence: 89%
“…The prevalance of preterm birth, SGA and LBW in our cohort was 17.3%, 40.3% and 42.3%, respectively, which was in concordance with the increased incidence of preterm birth, LBW and intrauterine growth retardation reported in PWS ( 26 , 27 , 28 ).…”
Section: Discussionsupporting
confidence: 89%
“…Intrauterine hypotonia causes polyhydramnios, malpresentation, and reduced fetal movements, leading to a higher probability of cesarean. All these features were found in this study, in accord with other reports ( 12 ).…”
Section: Discussionsupporting
confidence: 94%
“…It was reported that the full-term infants accounted for 80.4% of all 102 PWS patients. However, other studies have reported on the prevalence of preterm births and small for GA newborns ( 12 ). The discrepancies may be explained by the differences in sample size and ethnic differences.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the present study, we showed that the majority of children (83%) experienced early feeding issues. In keeping with existing data in PWS, 68% required NG feeding 4,33 . Specialised formula and thickened fluids were necessary and delays in achieving feeding milestones were reported in this group.…”
Section: Discussionsupporting
confidence: 65%